2007
DOI: 10.1111/j.1365-2435.2007.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effects and evolution at ecological time‐scales

Abstract: Summary1. Genetic and environmental maternal effects can play an important role in the evolutionary dynamics of a population: they may have a substantial impact on the rate and direction of genetic change in response to selection, and they may generate immediate phenotypic change via phenotypic plasticity. Because of this potential to generate rapid phenotypic change in a population, maternal effects may be particularly important for evolution at ecological time-scales. 2. Despite an increased interest in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
489
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(497 citation statements)
references
References 145 publications
(209 reference statements)
8
489
0
Order By: Relevance
“…In contrast, a negative cross‐generation genetic correlation between the traits, such as found here when selecting for delayed phenology, will counteract the environmental correlation, slowing the response to selection. This suggests that transgenerational effects constraining evolutionary change (e.g., Räsänen & Kruuk, 2007; Wilson & Réale, 2006) may have shaped the genetic correlation found between germination and flowering time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a negative cross‐generation genetic correlation between the traits, such as found here when selecting for delayed phenology, will counteract the environmental correlation, slowing the response to selection. This suggests that transgenerational effects constraining evolutionary change (e.g., Räsänen & Kruuk, 2007; Wilson & Réale, 2006) may have shaped the genetic correlation found between germination and flowering time.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of empirical studies have demonstrated that cross‐generation genetic correlations tend to be negative and act in opposition to within‐generation genetic correlations (Galloway, Etterson, & McGlothlin, 2009; Räsänen & Kruuk, 2007; Wilson & Réale, 2006). Opposing maternal–offspring genetic correlations can act as a constraint to rapid evolutionary change as they reduce the available additive genetic variation and as such may be favored during episodes of stabilizing selection (Wolf & Brodie, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Because maternal effects can generate alternative phenotypes in response to environmental fluctuations, this phenotypic change, Rubolini et al [174] i.e. plasticity, may be critical for responding to rapidly changing environments [188].…”
Section: Hormonally Mediated Maternal Effects On Dispersal and Populamentioning
confidence: 99%
“…Quantitative genetics models examine the evolution of parental provisioning of dependent offspring in terms of adaptive maternal effects, defined as environmental conditions generated by the parent that influences the expression of offspring traits such as growth and survival (Cheverud 1984;Kirkpatrick & Lande 1989;Cheverud & Moore 1994;Mousseau & Fox 1998;Räsänen & Kruuk 2007). Although maternal effects are defined as environmental sources of variation, they are likely to have a partially genetic basis, in which case they might evolve in response to selection (Kirkpatrick & Lande 1989).…”
Section: Behavioural Ecology Versus Quantitative Geneticsmentioning
confidence: 99%